Fullmetal alchemist. 15 - Arakawa, Hiromu, 1973- (Viz, 2007)
The horrors of the Ishbalan extermination campaign had serious repercussions, which set the tone for the complicated dealings of present-day state politics. Lieutenant Hawkeye reluctantly tells Ed all the dreaded details of the role Colonel Mustang and the other state alchemists played in this tragic event.